Hubungan Karakteristik dan Pengetahuan Ibu Tentang Stimulasi Terhadap Perkembangan Motorik Halus Anak Usia 3-5 Tahun di Desa Mireuk Lamreudeup - Riska Villina; Syukriadi Syukriadi; Ellyza fazlylawati (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
This study aims to determine the relationship between characteristics and maternal knowledge about stimulation of soft motor development in children aged 3-5 years in Mireuk Lamredeup Village. The research design used was observational with a cross-sectional approach. The sample was selected using a purposive sampling technique with a total sample of 52 respondents. Data collection techniques use questionnaires with knowledge questionnaire instruments and Pre-Developmental Screening Questionnaires (KPSP). Data analysis techniques use univariate and bivariate tests. The results of hypothesis testing using Chi Square obtained a sig value. calculate the mother's characteristics, namely education level (p= 0.005), age (p= 0.015), and mother's knowledge (p= 0.029). Based on the results of the hypothesis test, it was concluded: 1) there is a significant relationship between Mother’s age on the soft motor development of children aged 3-5 years; 2) there is a significant relationship between Mother’s education on the soft motor development of children aged 3-5 years; and 3) there is a significant relationship between mother's knowledge and the soft motor development of children aged 3-5 years.